Analysis of the Effectiveness of Social Media Campaigns in Promoting Healthy Lifestyles Among Teenagers - Dhias Widiastuti; Rahmi Sari Kasoema; Suyati; Dian Puspita Yani; Winarni (CV. Get Press Indonesia, 2024)
This study aims to analyse the effectiveness of a social media campaign in promoting healthy lifestyles among adolescents. This study used a quantitative approach with a survey method to measure the effectiveness, attitudes, and behaviours of social media campaigns in influencing healthy lifestyle awareness and attitudes among adolescents aged 15-19 years old. The sample will be taken using a purposive sampling technique involving 300 respondents who fulfil the criteria, namely adolescents who follow healthy lifestyle campaigns on social media. Data were processed to describe the profile of the respondents, their level of exposure to the campaign, and their general views on health behaviours. Bivariate analysis showed a significant association between health literacy and healthy behaviours (p = 0.002). Audio-visual media had the highest effectiveness rate (85%), followed by leaflets (65%). Audio visual media was found to be more effective in delivering campaign messages than leaflets, with an effectiveness rate of 85% compared to 40%. The results showed that health promotion through social media has great potential to encourage adolescents to lead a healthy lifestyle.